1966
DOI: 10.1042/bj1010302
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring anhydrovitamin A2. Transformation into retinene2

Abstract: 1. ;Naturally occurring anhydrovitamin A(2)' obtained from the liver oil of freshwater fish Bagarius bagarius yielded, after six-stage chromatography, a pure product showing characteristic bands at 350, 368 (E(1%) (1cm.) 1006) and 390mmu in ethanol, and producing a green colour with antimony trichloride (E(1%) (1cm.) 1884 at 693mmu). 2. On distribution of the material between light petroleum and 95% methanol, 70% of it is found in methanol, which points to its hydroxylic character. 3. It gives an acetyl deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1968
1968
1996
1996

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…However, it was observed that even these fish liver oils occasionally contain very little of the anhydro compound (Table 2). An attempt was made to confirm the 3-hydroxyanhydroretinol structure proposed by and Barua & Nayar (1966). It was found that the naturally occurring compound is always accompanied by a large quantity of sterols, which could be separated, except for a trace (as indicated by the mass spectrum), by repeatedly cooling the methanolic solution followed by treatment with digitonin.…”
Section: Metabolism Of 3-hydroxyretinol In S Fossilismentioning
confidence: 91%
See 2 more Smart Citations
“…However, it was observed that even these fish liver oils occasionally contain very little of the anhydro compound (Table 2). An attempt was made to confirm the 3-hydroxyanhydroretinol structure proposed by and Barua & Nayar (1966). It was found that the naturally occurring compound is always accompanied by a large quantity of sterols, which could be separated, except for a trace (as indicated by the mass spectrum), by repeatedly cooling the methanolic solution followed by treatment with digitonin.…”
Section: Metabolism Of 3-hydroxyretinol In S Fossilismentioning
confidence: 91%
“…From these observations Balasundaram et al (1958) reported that the naturally occurring anhydrovitamin A2 differed from the synthetic anhydrovitamin A2 (3-ethoxyanhydroretinol) in not having an ethoxy group, but having a different substituent in the 8-ionone ring or possibly elsewhere. Although and Barua & Nayar (1966) have proposed a 3hydroxyanhydroretinol structure, the structure has not so far been confirmed. Vol.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Another possible reaction pathway yielding first 3-dehydroretinol and then retinol is summarised below (from GROSS and BUDOWSKI, 1966 0<--~ '0<-- BARUA and NAYAR (1966) suggest that dietary hydroxy-carotenoids are converted into 3-dehydroretinaldehyde by way of the intermediate "naturally-occurring anhydrovitamin A 2 ", or 3-hydroxyanhydroretinol, which has been found in…”
Section: F Origins and Biogenesis Of The 3-dehydroretinol Prostheticmentioning
confidence: 99%
“…Vitamin A compounds possessing the retro system of conjugated double bonds have been encountered in biological samples (Balasundaram, Bamji, Cama, Sundaresan & Varma, 1958;Varma, Erdody & Murray, 1965a). The structure of the naturally occurring anhydrovitamin A2 was shown to be 3-hydroxyanhydrovitamin A1 (Barua & Nayar, 1966), whereas the chemically synthesized anhydrovitamin A2 was 3-ethoxyanhydrovitamin A1 (Henbest, Jones, Owen & Thaller, 1955a). When chemically synthesized anhydrovitamin A2 was fed to vitamin A-deficient rats, it gave rise to 'rehydrovitamin A2' (Balasundaram et al 1958;Bamji, Cama & Sundaresan, 1962).…”
mentioning
confidence: 99%